Studi Kapasitas Terminal Penumpang Bandar Udara Internasional Sultan Iskandar Muda - Aiyub, Aiyub (Portal: Jurnal Teknik Sipil, 2023)
Forecasting the number of passengers is very important to know in order to improve services in the security, comfort and passenger safety sectors. This research aims to determine the estimated number of passengers at Sultan Iskandar Muda International Airport and the need for passenger terminal facilities at Sultan Iskandar Muda International Airport in the next 10 years. The data used in this research is secondary data originating from PT Angkasa Pura II Sultan Iskandar Muda International Airport in the form of data on the number of passengers from 2010-2021, airport and passenger terminal plans, and passenger data at busy times. The calculation method for forecasting the number of passengers used is a simple linear regression analysis method. The research results show that the annual number of passengers will increase in 2031 by 640,530 people (an increase of 86.07% from 2019) for domestic arrivals, 260,556 people (an increase of 60.51% from 2019) for international arrivals, 692,256 people (an increase 96.98% from 2019) for domestic departures, 273099 people (an increase of 64.10% from 2019) for international departures, 64405 people (an increase of 58.62% from 2019) for domestic transit, and 169791 (an increase of 307% from 2019) people for international transit. The passenger terminal capacity requirements in 2031 for the baggage claim area, arrival hall, departure hall, waiting room, check-in area, check-in counter, seating and toilets are still below the existing capacity of the passenger terminal. The existing capacity of passenger terminal facilities based on SKEP.77/VI/2005 for Sultan Iskandar Muda International Airport is in the 'Medium' and 'Large' categories. Based on the existing capacity and area, the passenger terminal can still accommodate passenger movements for the next 10 years, namely until 2031.Keywords: capacity; number of passengers; passenger terminal; forecastin; simple linear regression.